Differentiation Of Canine Bone Marrow Mesenchymal Stem Cells Into Islet–Like Cells (Applied Biological Research, 2018)
The present study was aimed to study in vitro differentiation of canine bone  marrow mesenchymal stem cells (BMSCs) to islet-like cells of pancreas.  BMSCs were isolated from healthy dogs and cultured in laboratory. BMSCs  after 3rd passage (at 80% confluence) were induced to differentiate into islet like cells by using 2-step induction methods.Characterization of differentiated  cells of BMSC into islet-like cells was done by observing cell morphology,  expression of canine insulin gene by reverse transcriptase PCR (RT-PCR) and  quantitative PCR (qPCR), detection of nestin and insulin proteins by immunocytochemistry and quantification of insulin level in culture media.  Typical grape-like clusters of cells were observed under bright field  microscope. Expression of insulin gene and protein was observed in  differentiated cells. Insulin level in culture media of differentiated cells was  significantly high. It was concluded that canine BMSCs could effectively be  differentiated into islet-like cells. These differentiated cells could play an  important role in diabetic therapy of dogs.
Keywords: BMSCs; differentiation; dogs; islet-like cells